Leaving home, family support and intergenerational ties in Italy: Some regional differences - Elisabetta Santarelli; Francesco Cottone (Demographic Research, 2009)
In Italy conditions at leaving home are characterized by high age at exit, high proximity with parents and widespread intergenerational support, showing important regional differences. According to the "familistic" approach such conditions spread from strong intergenerational ties. Proximity and support are considered proxies of ties' strength so that different regional proximity and support correspond to different ties' intensities. The study aims at analyzing similarities and differences about parent-child ties, proximity and support in selected Italian regions, Liguria, Umbria, Sicily and Sardinia. Results show important differences among regions with respect to proximity and support, suggesting different intensity of intergenerational ties.